Inclusive Enrichment for Dragons: Behavioral Responses of Amputee and Non-Amputee Individuals of Bearded Dragons Pogona vitticeps to Different Food Enrichment Items - Luisa Martins Pereira; Cristiano Schetini de Azevedo; Helen Colbachini; Cynthia Fernandes Cipreste; Maria Eduarda Schilbach Pizzutto; Laura Chrispim Reisfeld; Rafael Capriolli Gutierrez; Fabiana Lúcia André Padilha; Cristiane Schilbach Pizzutto (Journal of Zoological and Botanical Gardens, 2024)
Studies on environmental enrichment for captive bearded dragons (Pogona vitticeps) are still very scarce in the literature, but they are of the utmost importance in the search for quality of life for these animals when they are under human care. Environmental enrichment items should be inclusive, allowing disabled animals to explore them and providing good experiences. Therefore, this study aimed to evaluate food enrichment strategies to increase the foraging behavior of captive non-disabled and disabled bearded dragons. This work was carried out with six adult bearded dragons, three of which had one limb amputated and three that had all limbs, kept at the São Paulo Aquarium. Live kingworm larvae (Zophobas morio) were offered as food in three different levels of enrichment challenge (low, medium, high). Behavioral data were collected using focal sampling with instantaneous recording, with a time interval of every 30 s. Results showed that the more complex the food enrichment challenge, the greater the frequency of bearded dragon foraging. In addition, both amputees and non-amputees responded similarly to the enrichment items, differing primarily in their activity levels, where amputee individuals showed more tendencies toward ‘stationary’ and ‘lying down’ behaviors. More studies with reptiles should be encouraged so that good management practices become daily protocols for a better quality of life and for rescuing the natural behaviors of animals kept under human care, even those with anatomical disabilities.